FLOUTING MAXIMS ON THE DIALOGUE OF CHARACTERS IN UP! ANIMATED MOVIE - Perni Giriyani; Efransyah Efransyah (IKIP Siliwangi, 2020)
This research is about flouting maxims on the dialogue of characters in UP! Animated movie. Hence, it is aimed to know flouting maxim on UP! animated movie. This research is used qualitative research. The data of this study was taken on flouting maxims on the discourse of figure in UP! animated movie from he main characters namely old name Carl Fredrickson and Russel. There are several steps in collecting the data namely, finding a script UP! of the animated movie, next is analyzing the script with the UP! movie and the last is to list the utterances of the main personality of UP! animated movie in flouted maxims and finally analyzing them based on the chosen theory. After conducting the research, the writer found 20 sentences that flouted by Mr. Fredickson and Russel animated UP! movie. Those kinds of maxims are 6 flouted maxims of quantity, 7 flouted maxims of quality, 3 flouted maxims of relevance, and 4 flouted maxims of manner. Keywords: Flouting maxim, Dialogue, Movie